2005
DOI: 10.3171/foc.2005.18.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of carotid artery disease after radiation therapy and radical neck dissection

Abstract: Object More patients with head and neck cancers who undergo radical neck dissection and adjuvant radiation are experiencing prolonged survival times. Because of their improved survival, patients are living long enough to suffer the delayed effects of radiation therapy. Radiation-induced carotid artery (CA) stenosis in patients with or without radical neck dissection often requires extensive exposure and vessel reconstruction. The aim of this study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…27 Similar to other reports, we have found that open carotid repair can be performed safely with no early death, and low stroke (4%) and restenosis rates (11%). 4,[6][7][8][9][10][11][12][13][31][32][33] Conversely, carotid stents may not be as durable as open carotid repair in the radiated neck. Protack et al 12 reported restenosis in 43% of 23 patients treated for radiation-induced lesions with carotid stenting, including two (8.5%) who had stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Similar to other reports, we have found that open carotid repair can be performed safely with no early death, and low stroke (4%) and restenosis rates (11%). 4,[6][7][8][9][10][11][12][13][31][32][33] Conversely, carotid stents may not be as durable as open carotid repair in the radiated neck. Protack et al 12 reported restenosis in 43% of 23 patients treated for radiation-induced lesions with carotid stenting, including two (8.5%) who had stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…It avoids the need to dissect through scarred tissue and the potential risks of cranial nerve injury or wound healing complications. 4,[6][7][8][9][10][11][12][13] However, the enthusiasm with CAS has been tempered by high rates of restenosis and reinterventions in the range of 4% to 51% in contemporary reports dealing with radiation-induced carotid stenosis (RICS). 4,[8][9][10]6,12,13 The aim of this study was to review the outcomes of CAS and of a historical group treated with open carotid repair (OR) for RICS.…”
mentioning
confidence: 99%
“…Simultaneously, the risk for relevant carotid stenosis seems to increase. 42 Several carotid intervention studies defined Ecker et al 27 patients undergoing XRT as a high-risk group for CEA. 2,43,44 This classification remains controversial because the definition was based on theoretical arguments and still no risk stratification for patients undergoing XRT exists today.…”
Section: Discussionmentioning
confidence: 99%
“…Large differences among studies existed. Two small studies 17,27 (nϭ5 and nϭ7) found no restenosis and no reinterventions performed during follow-up (9.3 and 6.0 months). Two slightly larger studies both monitored 16 patients for, respectively, 30 and 28 months and found restenosis rates of 17.6% and 21.0%.…”
Section: Restenosismentioning
confidence: 99%
“…With the further development of new stent devices, delivery techniques, and cerebral protection devices, the use of CAS for the treatment of radiation-induced carotid stenosis will become safer and more durable [46]. …”
Section: Treatmentmentioning
confidence: 99%